Letter Writing of Dr. Aslam Ansari - Shaista Awan (بازیافت, 2023)
<span style="font-size: 12.0pt; line-height: 107%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: "Jameel Noori Nastaleeq"; mso-hansi-theme-font: minor-latin; mso-bidi-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: ER;">Writing letters is a fantastic way to keep the mind active as it helps to improve memory, concentration and communication skills. Research suggests that writing letters to your nearest and dearest can help you feel happier and more satisfied. Letter writing is an important genre in Urdu Literature. The art of letter writing, formal and informal, has made many a people well known in the literary circles. Dr. Aslam Ansari, one of Urdu's famous poet, critic and researcher, has also enriched the world of literature with his letters. They are insightful in terms of literature and criticism. He used his letters not only as a means of communication but also highlighted many intellectual aspects. In this article, a review of Aslam Ansari's letters is being presented for the first time.